Possibilidades de mediação dos espaços nas brincadeiras e aprendizagens das crianças na educação infantil - Sitta, Kellen Fabiana (2008)
To understand the recent conceptions about childhood we have, necessarily, to seek in the historical aspects some answers for the present, due to the fact that a childhood vision also has historical and cultural relation, according to the Historical-cultural theory that grounded this research. In the long route of the history of attendance to childhood, researches and practices have been searching to affirm the importance of promoting a good quality education to all children - that involves diverse aspects of attendance, such as the ambient built. This work departed of the conception that the physical space of the infantile schools, appropriated at leisure activities of the children, can become a mediator of big relevance in the process of learning and development. Such being the case, the research matter that oriented this study was the following: What aspects are involved in the everyday of infantile schools so that the different spaces and equipments could work as mediators of the games of all children? The particular objective were: to diagnose the spaces (inside and outside) in the Infantile Schools of the municipal district of São Carlos; find out at schools which spaces are appropriated for games; analyze how those spaces are organized for the children plays and to identify/to analyze the mediation possibilities of the spaces in the learning and plays of the children. We used as a reference the Historical-cultural Theory because it acknowledge the game like main activity in the preschool phase, as long as for intermediate of it occur the most important changes in the psychic development of the child. The methodology used for the data collecting chose three different instruments: the first was a questionnaire applied at an extension activity about plays, at about 300 teachers of municipal district of São Carlos (SP), accomplished in the UFSCar (2006). The second instrument was a field research, in which was applied a questionnaire at 27 director of Infantile schools, about the physical structure of the schools and the activities accomplished in those spaces and; the third were observations of the games in the physical spaces of two units school. For the analysis of the data was chosen an only guideline that directed the over deepening of our glance in the specificities hinted by the data from the different instruments: the space like mediator of the playfully activities. Starting of that guideline could enlarge the analysis in four subguidelines, are they: 1. Physical structure - Quality of the spaces and learning of the children; 2. The outward and internal spaces like mediators of the activity kinds of the children; 3. Space, Game and Toys: the quality of the learning of the children and 4. The directed activities, the spaces and the teacher like mediator of the learning of the children. It is needed a profound reflection about insufficiencies interrelated to infra-structure and organization of the spaces in the Infantile institutions, conceiving that this is a big relevance factor in the mediation of the learning of the children. Our research also suggests that the space influence the teacher and contrary, being a reciprocal and continues motion.